FACTORS AFFECTING LABOR DURATION IN PREGNANT WOMEN AT NGHE AN GENERAL HOSPITAL, 2022 - Cao Ba Loi; Tran Thi Kieu Anh; Truong Van Tu (JOURNAL OF CONTROL VACCINES AND BIOLOGICALS, 2024)
The aim of the study was to describe clinical characteristics, labor duration, factors related to the labor duration and effects of the labor duration on women with full-term, varginal delivery at the Obstetrics and Gynecology Department of Nghe An General Hospital in 2022.Cross-sectional descriptive study with analysis. Results: A total of 295 pregnant women at the Department of Obstetrics and Gynecology, Nghe An General Hospital were included in the study. Data were collected using a pre-designed medical record form. Results showed that the average BMI was 25.47 ± 2.31. Commonly seen signs of labor included dull belly pain (44.1%); pinkish discharge or blood show (33.5%). The average labor duration of primiparous pregnant women was 19.32 ± 12.19 hours; of multiparous pregnant women was 11.90 ± 7.90 hours. The rate of urinary retention was 13.5%; postpartum hemorrhage was 2.4%; and artificial rupture of membranes was 73.2%. There was a weak positive correlation (r = 0.284, p<0.001, R2 = 8.1%) between maternal BMI and Stage 1a labor duration; the pregnant women with BMI > 30 had the longest Stage 1a labor duration (p < 0.05). Prolonged labor is an increased labor duration compared to pregnant women with same risk factors. Prolonged labor can lead to serious complications or sequelae if it is not early detected and promptly treated. Possible complications includes: fetal distress, potential of uterine rupture, uterine rupture, bladder or rectal fistula, neonatal infection, and postpartum infection. Therefore, monitoring of labor process and detection of possible problems should reduce complications affecting the mother’s health during labor.